Shell and tube heat exchanger optimization: A critical literature assessment and fairness-based comparative performance analysis of meta-heuristic algorithms - Samet Gürgen (Case Studies in Thermal Engineering)
Determining the optimum design of shell and tube heat exchangers (STHE) is a crucial issue for the efficient use of scarce energy resources. In particular, there is a great effort on the economic-based optimization of STHE. The most well-known STHE design in the literature is the one presented by Sinnot et al. This design problem has been addressed by many researchers with different optimization algorithms. In the first part of this study, an optimization study was conducted using a limited set of algorithms for the same optimization problem. In order to make comparisons, the objective function, decision variables and their boundary values were taken as the same. Initial findings showed that the results were quite close to each other, contrary to the literature. It was determined that the variability in the results of previous studies was due to differences in the mathematical model and incorrect optimization procedure. In the second part of the study, a comprehensive algorithm performance analysis of twenty meta-heuristic optimization algorithms was performed. This study aimed to perform algorithm performance for STHE optimization by integrating a fair evaluation approach. It also offers a robust framework for effectively using and comparing optimization algorithms in thermal engineering applications.